DEVELOPMENT OF EXPLORATIVE MATHLET LEARNING MEDIA BASED ON ADOBE FLASH CS6 WITH ISLAMIC NUANCES ON LINEAR EQUATIONS SYSTEM WITH THREE VARIABLES MATERIAL: PENGEMBANGAN MEDIA PEMBELAJARAN MATHLET EKSPLORATIF BERBASIS ADOBE FLASH CS6 BERNUANSA ISLAMI PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Andi Mattoliang, Lisnasari; Baharuddin; Muhammad Jabal An Nur; Riswandi, Akmal (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to produce explorative mathlet learning media based on adobe flash CS6 with Islamic nuances on the linear equation system with three variables material and to determine the level of validity, practicality, and effectiveness of the media. The type of research used is research and development concerning the development model of Alessi and Trollip. The stages of multimedia development consist of: (1) the planning stage, (2) the design stage, and (3) the development stage. The test subjects in this study were students of class X MA Madani Alauddin Pao-Pao. The instruments in this study were expert validation sheets, observation sheets on the implementation of the device, student response questionnaires, student activity observation sheets, and learning achievement tests. The results showed that the explorative mathlet learning media based on adobe flash CS6 with Islamic nuances on the linear equation system with three variables material met the valid, practical, and effective criteria. Thus, the results of this study imply that learning media can be used as an alternative to improving students learning outcomes.